Calculation method for CO2 geological storage capacity of fault-block traps in Subei Basin based on safety considerations - SUN Dongsheng, ZHANG Shunkang, WANG Zhilin, GE Zhengjun, LIN Bo (Youqicang pingjia yu kaifa)
To address the safety concerns associated with the CO2 geological storage process in fault-block traps of the Subei Basin, safety thresholds were systematically determined by integrating fault sealing capacity, caprock integrity, and wellbore stability through theoretical calculations and laboratory experiments. In terms of fault sealing, a fault connectivity probability model was established. For caprock integrity, the critical breakthrough pressure was determined through experimental testing. Regarding wellbore safety, standards for CO2 injection into old wells were formulated. Based on the identified safety thresholds of faults, caprocks, and wellbores, numerical simulation techniques were used to simulate CO2 geological storage and calculate the storage capacity. During the simulation, the model ceased computation when pressure conditions of faults, caprocks, or wellbores reached their safety thresholds. A calculation method for the CO2 geological storage capacity in fault-block traps in the Subei Basin was established by calculating the CO2 storage volume in the simulation model and analyzing key parameters such as the pore volume occupancy of storage locations. Two injection strategies, continuous gas injection and water-alternating-gas injection, were employed to calculate the CO2 geological storage capacity in a specific fault-block trap in the Subei Basin. The results indicated that the opening pressures of the main controlling faults in this trap were 42.9 MPa and 44.8 MPa, respectively. The maximum breakthrough pressure of the caprock reached 40.5 MPa, and the casing failure pressure was 45 MPa. The storage coefficients were 0.04 t/m3 for continuous gas injection and 0.03 t/m3 for water-alternating-gas injection. During water-alternating-gas injection, the pressure increased more slowly than in continuous gas injection due to partial extraction of formation water by production wells, resulting in a higher final CO2 storage capacity. However, due to a significant increase in the pore volume occupied by CO2 under the water-alternating-gas injection strategy, the CO2 storage coefficient was lower than that of continuous gas injection.